Pulmonary ultrasound: Diagnostic possibilities for interstitial lung disease associated with rheumatoid arthritis - R. R. Ahunova; G. R. Ahunova (Научно-практическая ревматология)
Interstitial lung disease associated with rheumatoid arthritis (RA-ILD) is one of the systemic manifestations of rheumatoid arthritis (RA) associated with high mortality. According to the latest data, the prevalence of RA-ILD is 3–4%. 26% of patients with RA-ILD develop a progressive interstitial lung disease (ILD) phenotype. To date, for the diagnosis of ILD, including in RA, the ultrasound method of research is being intensively introduced. Ultrasonography of the lungs is a useful adjunct to high-resolution computed tomography (HRCT) and an affordable aid for frequent use. The advantages of lung ultrasound are high information content, reproducibility, ease of use, speed of execution, prognostic value, absence of ionizing radiation. Identification of B-lines in various variants, an uneven, thickened, discontinuous pleural line, and/or delimited cortical consolidations in the form of hypoechoic small areas during ultrasound of the lungs in RA patients can help to promptly suspect ILD and send them to HRCT. The simple and uncomplicated research technology makes it attractive for monitoring the progression of pulmonary fibrosis. The use of ultrasound is necessary, in particular, in the presence of a progressive ILD phenotype, confirmed by HRCT, for conducting serial studies in order to monitor the progression of the disease.